A new family, genus and species of freshwater amphipod Australomicroprotopus megacoxa gen. nov. sp. nov. (Senticaudata, Corophiidea, Microprotopoidea, Australomicroprotopidae fam. nov.) from Australia - Myers, Alan A.; Lowry, James K.; Billingham, Zac (Zootaxa, 2016)
A new species of fresh-water amphipod is described from Australia. Australomicroprotopus megacoxa gen. nov. sp. nov. It is placed in a new family, the Australomicroprotopidae fam. nov. and is fully described and figured.